The Theory-Practice Relationship. A Teaching Experience during the Last Workshop at the Faculty of Architecture, UNNE, Argentina - Giró, Marta Graciela (Revista INVI, 2006)
We will present a teaching experience known as "Free Teachers in Architecture V Class within the Architecture Department of the National University of the Northeast3 ". Architecture V is a class from the career's last Design Workshop, and its main focus is the development of a Final Project to be completed by the students. This Project should: • Determine the main topics/problems that will be discussed. • Carry out an investigation on the chosen topics/ problems. • Present a proposal. In each case, the topics are to be in relation to a demand from a Governmental or Non-Governmental entity, or simply to the students' concerns. All the activities mentioned above are to be completed by the students, using the class exclusively as a tutorial, for methodological and theoretical support. Within these lines we have developed this experience, which attempted to provide methodological support for all of the students' projects. This article is an effort to reflect on the subject, which appeared through the need/difficulty to work with contents related to "methodological strategies" employed to discuss the problems, complexity4, transdisciplinarity, and group work.